2021
DOI: 10.1177/19386400211045911
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic and Clinical Results of Minimally Invasive Chevron Akin Osteotomy for Moderate to Severe Hallux Valgus Deformities

Abstract: Background: Few studies have reported results of minimally invasive chevron Akin osteotomy (MICA) for moderate to severe hallux valgus correction. This study aims to evaluate MICA for moderate to severe hallux valgus radiographically and clinically. Methods: Forty feet were prospectively reviewed. Twenty-eight feet (70%) had a severe deformity (hallux valgus angle (HVA) ≥40° and/or first intermetatarsal angle (IMA) ≥18°). We measured HVA, IMA, lateral shape of the metatarsal head (round sign), tibial sesamoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Three studies reported significant improvements in the Foot Function Index, Japanese Society for Surgery of the Foot Scale, and Manchester-Oxford Foot Questionnaire scores, which are comparable to the AOFAS score. 2 , 17 , 27 One study did not report AOFAS or any comparable score. 29 Preoperative and last follow-up visual analog scale (VAS) score was reported in 7 studies, and in 5 it was reported as statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported significant improvements in the Foot Function Index, Japanese Society for Surgery of the Foot Scale, and Manchester-Oxford Foot Questionnaire scores, which are comparable to the AOFAS score. 2 , 17 , 27 One study did not report AOFAS or any comparable score. 29 Preoperative and last follow-up visual analog scale (VAS) score was reported in 7 studies, and in 5 it was reported as statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…The preoperative HVA was 29.3 degrees and improved to 7.1 (4-12) degrees postoperatively. The mean IPA improved from 13.5 (9)(10)(11)(12)(13)(14)(15)(16) degrees to 4.7 (3-8) degrees postoperatively. The preoperative IMA, HVA, and IPA differences between the fracture and nonfracture group were not significant (P > .05).…”
Section: Primary Outcomesmentioning
confidence: 90%
“…Overall, studies have reported similar outcomes with effective deformity correction, short learning curve, low complication rate, low symptomatic recurrence, low postoperative opioid use, and high patient satisfaction. 3,9,[11][12][13][14][15]17,18,22 Although this study focused on a third-generation technique with rigid, permanent fixation, there are multiple techniques for the percutaneous Akin throughout the Reports of undesired lateral cortex fracture are ubiquitous throughout the literature. 1,[7][8][9] Lateral hinge fractures have been thought to contribute to osteotomy instability and secondary displacement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Potential limitations of these procedures include shortening of the metatarsal bone due to the thickness of the burr, imprecise bone cuts, thermal injuries to the bone and wound edges, injuries to proximal nerves (eg, the dorsal medial cutaneous nerve possibly due to the catching and "wrapping" of the nerve with the burr), and injuries to the metatarsal head vascular supply and the flexor and extensor tendons. Kurashige 20 studied the radiographic and clinical results after MICA for moderate-to-severe HV deformities. Overall results were satisfactory; however, they reported an overall complication rate of 32.5% and there were undercorrections and bony prominences in 7.5% of cases.…”
Section: Discussionmentioning
confidence: 99%